Pengaruh Budaya Kerja dan Motivasi Kerja terhadap Kinerja Pegawai Badan Perencanaan Pembangunan Daerah Provinsi Jambi - M. Pandu Jaya Kafilatullah; Zulfina Adriani; Fitri Widiastuti (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study aims to determine the positive influence of work culture and work motivation on employee performance at the Regional Development Planning Agency (BAPPEDA) in Jambi Province. This study is an associative study that examines the relationship between two variables. The subjects were 86 employees at the BAPPEDA office. Data collection was conducted using a questionnaire. Data were analyzed using a Likert scale and statistically processed using statistical tests and SPSS version 26 for Windows. Based on the research results, it can be obtained that the work culture variables (X1) and work motivation (X2) have a positive and significant effect on employee performance (Y) of the Jambi Province Regional Development Planning Agency, with the results of the t test obtained for the work culture variable obtained a calculated t value> t table (2.668> 1.988) with a significant level of 0.009 <0.05 and for the work motivation variable obtained a calculated t value> t table (2.192> 1.988) with a significant level of 0.031 <0.05 it can be concluded that the factors (work culture and work motivation) partially influence employee performance at the Jambi Province Regional Development Planning Agency, and the F test obtained a calculated F value> F table (17.938> 3.103) it can be concluded that the work culture variable (X1) and the work motivation variable (X2) simultaneously have a positive and significant effect on employee performance.